GENETIC PREDICTORS OF SEVERITY AND EFFICACY OF COVID-19 PHARMACOTHERAPY - I. N. Shishimorov; O, V. Magnitskaya; Yu. V. Ponomareva (Фармация и фармакология (Пятигорск))
The pandemic of the novel coronavirus infection 2019 (COVID-19) has changed many aspects of our lives and initiated numerous studies aimed at finding the factors that determine different courses of this infectious disease. The studies aimed at finding predictors of the severe course of this novel coronavirus infection, as well as the factors that determine the efficacy and safety of this disease pharmacotherapy, are acquiring special social significance.The aim of this work is to find and summarize information on genetic predictors of severe COVID-19, as well as pharmacogenetic aspects that determine the variability of the therapeutic response to the drugs recommended for COVID-19 treatment.Materials and methods. The article provides a review of scientific results on the research of gene polymorphism that determine a body’s response to the introduction of SARS-CoV-2 infection and the effects of pharmacotherapy for this disease, obtained from open and available sources within the period of 2019 – March 2021. The search was conducted in the following electronic databases: PubMed, Cochrane Library, ClinicalTrials.gov; Elibrary, Scopus. The main search inquiries were: “predictors + severe course + COVID-19”, “genetic variations + COVID-19”, “pharmacogenetics + COVID-19”, “gene polymorphism + SARS-CoV-2”, “pharmacotherapy + gene polymorphism + COVID-19” in both Russian and English.Results and conclusion. The exploratory research detailing the mechanisms of infecting with SARS-CoV-2, the variability of the disease severity and the individual characteristics of therapeutic responses to the drugs used, are being actively carried out by scientists all over the world. However, most of their scientific projects are diverse, and the possible predictors of a severe course of COVID-19 found in them, have not been confirmed or investigated in subsequent studies. A generalization of the individual studies results of the genetic predictors concerning COVID-19 severity and effectiveness of its pharmacotherapy, can become the basis for further search and increase the reliability of the data obtained in order to develop a strategy for preventing the spread of COVID-19 infection, to identify potential targets of the treatment, and develop the protocols for optimizing this disease pharmacotherapy.